JUDICIAL REVIEW PRESIDENTIAL REGULATION ON THE 1945 NRI CONSTITUTION - Erickatama, Andrian; Setiadi, Wicipto (NOMOI Law Review, 2024)
With the existence of Article 9 paragraph of Law no. 13 of 2022 which only provides restrictions that only the Law can carry out a Judicial Review of the 1945 Constitution of the Republic of Indonesia, and Judicial Review of Government Regulations and Presidential Regulations can only be carried out on Laws, will close the way for a possible Judicial Review of the Independent Presidential Decree to be carried out on the contrary to the 1945 Constitution of the Republic of Indonesia. This research uses a normative method with a qualitative approach. The approach used in this research is a statutory approach and a conceptual approach. In exercising attribution authority, it is possible that there may be a Presidential Regulation that exceeds the authority of a President, or could potentially become a tool for abuse of authority by the President. There is a need for a correction mechanism in the form of a Judicial Review of the Independent Presidential Decree on the 1945 Constitution of the Republic of Indonesia as a mechanism for public control.